Prenatal diagnosis of congenital heart defects: accuracy and discrepancies in a multicenter cohort. (May 2016) - van Velzen, C. L.; Clur, S. A.; Rijlaarsdam, M. E. B.; Pajkrt, E.; Bax, C. J.; Hruda, J.; de Groot, C. J. M.; Blom, N. A.; Haak, M. C.
ABSTRACT: Objective: To examine the accuracy of fetal echocardiography in diagnosing congenital heart disease (CHD) at the fetal medicine units of three tertiary care centers. Methods: This was a multicenter cohort study of tertiary echocardiography referrals between 2002 and 2012. Prenatal and postnatal diagnoses were compared and the degree of agreement was classified as 'correct' (anatomy correct and the postnatal diagnosis led to a similar outcome as expected), 'discrepant' (anatomical discrepancies present but the severity and prognosis of the defect were diagnosed correctly) or 'no similarity' (the pre‐ and postnatal diagnoses differed completely). Results: We included 708 cases with CHD for which both prenatal and postnatal data were available. The prenatal diagnosis was correct in 82.1% of cases and discrepancies present were present in 9.9%; however, these did not result in a different outcome. In 8.1% there was no similarity between prenatal and postnatal diagnoses. Disagreement between pre‐ and postnatal diagnoses occurred significantly more frequently in cases that presented with a normal four‐chamber view than in those with an abnormal four‐chamber view (5.5% vs 1.9%). Incorrect identification of the outflow tracts and incorrect differentiation between unbalanced atrioventricular septal defect and hypoplastic left heart syndrome were relatively commonly encountered. In many cases with disagreement, trisomy 21, extracardiac anomaly or a high maternal body mass index was present. Conclusions: The prenatal diagnosis and estimated prognosis of fetal echocardiography in our tertiary referral centers were appropriate in 92% of cases. Some types of CHD remain difficult to diagnose or rule‐out prenatally, therefore awareness and education are of considerable importance. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.